2023
DOI: 10.18621/eurj.1241667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine supplementation during treadmill exercise on hippocampal genes expression levels in adolescent rats

Abstract: Objectives: The usage of caffeine, a psychostimulant that is included in many foods and drinks, is rising, especially among young people. Also, caffeine works as an ergogenic substance during exercise to improve performance, and strength. In this study, our aim was to investigate the effect of caffeine consumption and exercise on hippocampal learning and memory functions in early life. Methods: Postnatal 28 days old Wistar albino male rats (n = 28) were randomly divided into 4 groups; control group (C), caffei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Using the same caffeine administration protocol (0.25 mg/ml in drinking water beginning at P28), we have previously observed that caffeine increases the time spent in the light in a light/dark test in males but not females (Turgeon et al ., 2016) and produced a similar trend in a subsequent study (Nelson et al ., 2019); however, a similar protocol (0.3 mg/ml) produced anxiogenic behavior in males in the elevated plus maze (Ardais et al ., 2014). In addition, a more recent study found that a 4-week caffeine exposure of 0.3 mg/ml in drinking water beginning at P28 failed to alter the amount of center time in an open field in males (Bakir et al ., 2023). The present data may suggest caffeine-induced decreases in anxiety-like behavior as was observed previously in the light/dark task; however, the current results support a more robust effect in females than males given the larger caffeine-induced decrease in nontargeted burying and increase in active behavior in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same caffeine administration protocol (0.25 mg/ml in drinking water beginning at P28), we have previously observed that caffeine increases the time spent in the light in a light/dark test in males but not females (Turgeon et al ., 2016) and produced a similar trend in a subsequent study (Nelson et al ., 2019); however, a similar protocol (0.3 mg/ml) produced anxiogenic behavior in males in the elevated plus maze (Ardais et al ., 2014). In addition, a more recent study found that a 4-week caffeine exposure of 0.3 mg/ml in drinking water beginning at P28 failed to alter the amount of center time in an open field in males (Bakir et al ., 2023). The present data may suggest caffeine-induced decreases in anxiety-like behavior as was observed previously in the light/dark task; however, the current results support a more robust effect in females than males given the larger caffeine-induced decrease in nontargeted burying and increase in active behavior in females.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of behavioral results suggests potential anxiolytic-like and antidepressant-ike effects of caffeine during adolescence. The anxiolytic effects that were seen in the light/dark task, however, were not seen in the elevated plus maze (Turgeon et al ., 2016) or in center time in an open-field test (Bakir et al ., 2023). In addition, while behavior in the FST has long been considered to be reflective of affective state given the repeated demonstration of decreased immobility following antidepressant drug administration (Porsolt et al ., 1977) and increased immobility following prodepressant manipulations such as stress and corticosterone injections (Kalynchuk et al ., 2004; Johnson et al ., 2006; Veenema et al ., 2006), others have noted that increased immobility in the FST could be argued to reflect an adaptive response following learning that escape is not possible but rescue will occur (De Pablo et al ., 1989; West, 1990).…”
Section: Introductionmentioning
confidence: 99%